Memorization strategy and foreign language learning: a narrative literature review - Wang, Qunfeng (Frontiers in Psychology, 2023)
Memorization strategy as a subset of language learning strategy (LLS) has long been investigated to explain foreign language learners’ learning behaviors and uncover the role that it plays in foreign language learning (FLL). In the past half century, the focus of memorization research in FLL has been shifted from Memorization, Vocabulary Memorization to Text Memorization, which are termed with consideration of the length of language material to memorize. Since memorization strategy use is greatly influenced by varieties of psychological and socio-culture variables, the memorization strategy system becomes more complicated in the process of FLL. The present narrative review attempts to provide an overview of memorization strategy research in the field of FLL by discussing the concepts, categorizations, uses, instructions and influential factors of the three types of memorization strategies. By reviewing the existing studies, this paper proposes that in future research, diversified methods be deployed with the expansion of research perspectives and the enrichment of research topics to reveal the relationship between memorization strategy and FLL more extensively.